Pengaruh Kualitas Website dan Kepercayaan Konsumen terhadap Minat Beli pada E-Commerce Tokopedia di Surabaya - Dahlan, Ahsan Dlonni; Dermawan, Rizky; Zawawi, Zawawi (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
his study intends to understand how the impact of website quality and customer trust on purchase intentiom at Tokopedia e-commerce in Surabaya. The technique of this research is quantitative by using a sample of 105 answers which are determined based on a sampling technique based on guidelines according to Cochran. The population taken is Surabaya residents who have visited the Tokopedia website. The sample used was taken through purposive sampling. Sampling uses informants who have visited the Tokopedia online store at least once. The information used in the research is primary and secondary information. The method of analysis applied to this research is (PLS) with Validity Test, Reliability Test and Hypothesis Test. The results prove that Website Quality has a positive and significant influence on purchase intention. Customer trust has a significant positive impact on purchase intention. Keywords: Consumer Trust; Purchase Intention; Website Quality.